EVALUASI TATA KELOLA KEAMANAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 (STUDI KASUS PADA DINAS KOMUNIKASI DAN INFORMASI KABUPATEN SUMEDANG) - Yedi Setiadi (Scientia Regendi, 2022)
The Sumedang Regency Communication, Informatics, Statistics and Encoding Service is a regional apparatus that functions as a means of disseminating information to the wider community regarding public information, Service Information and digital services in developing Sumedang Regency based on Smart City. One of the factors that play a very important role in supporting business goals and processes is the existence of Information Technology facilities. Information technology governance is the structure of relationships and processes to direct and control the organization in achieving its objectives, in this case by adding value when balancing risk compared to IT and its processes. Information technology governance recommendations are made to improve performance carried out by Diskominfosandistik. The data collection process is carried out by distributing questionnaires to determine the current maturity level and the expected maturity level. With good information technology management, it is expected to produce good work procedures in supporting the achievement of the objectives of the Sumedang Discominfosandistik. Based on the calculation results, a decision can be made that the capability level at the Sumedang District Discominfodistik is at level 2 and has a gap of 1. After an audit has been carried out by calculating the capability level for the EDM, APO, BAI and DSS domains, the average value is obtained. is at level 2 (managed), with these conditions indicating that the Sumedang Regency Diskominfodistik already has a management information system. However, there are still some regulations regarding the implementation of the process that have not been fully implemented